Tissue thermometry during ultrasound exposure - Unger, E.; Hynynen, K.; Damianou, Christakis A.; Darkazanli, A.; Schenck, J. F. (My University, 1993)
In order to quantify ultrasound therapy it is important to measure the tissue temperature during the treatment. Invasive probes induce several artifacts in ultrasound fields. The magnitude of these artifacts is probe dependent. Several different probes were evaluated for hyperthermia purposes in this study. An alternative noninvasive method to evaluate the temperature elevations and tissue damage is to use magnetic resonance imaging. The fast imaging sequences used in this study are marginally useful for monitoring hyperthermia. However, these imaging sequences can be utilized to guide and monitor ultrasound surgery.
Keywords: Hyperthermia; Magnetic resonance; Surgery; Temperature; Ultrasound